The handbook of local government law in the Philippines - Madrona, Severo Cañete, Jr. (Quezon City Central Books Supply, 2021)
This handbook is the product of the author’s experience as the City Legal Officer of a highly urbanized city in Metropolitan Manila. The interaction with the local chief executive, Sangguniang Panlungsod, and the various department heads helped him unravel the intricacies of the local governance framework. Through the extensive discourse with concerned local officials, he was able to appreciate the goal of local autonomy, enabling local government units as self-reliant communities and effective partners in the attainment of national goals. The author acknowledges the unfaltering support of then Pasay City Mayor Antonino G. Calixto and current Pasay City Mayor Imelda Calixto-Rubiano.
Chapter 1 Autonomy of Local government -- Chapter 2 Powers of the Local Government -- Chapter 3 Local Govenment Officials -- Chapter IV Fiscal Autonomy and Local Sources of Funds.
Keywords: Local government -- Law and legislation -- Philippines